2021
DOI: 10.3389/fmed.2021.747720
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between the Choroidal Vascularity Index and Malignant Glaucoma After Trabeculectomy for Primary Angle Closure Glaucoma

Abstract: Purpose: To compare the choroidal vasculature characteristics by using the choroidal vascularity index (CVI) in eyes with malignant glaucoma (MG), fellow eyes with non-MG, and eyes with uncomplicated primary angle-closure glaucoma (PACG) after trabeculectomy by spectral-domain optical coherence tomography (SD-OCT).Methods: This case–control study included 53 patients diagnosed with MG after trabeculectomy. Eyes with MG (n = 53) and the fellow eyes with non-MG (n = 50) were included. Eyes with PACG without MG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…39 Similarly, our findings showed that higher IOP was significantly related to lower CVI, although many studies suggest that CVI is relatively unaffected by various factors. 14,15 We hypothesize that elevated IOP has a mechanical effect on the choroid and its vascularity. The hypothesized mechanism is that high IOP can cause mechanical stress and deformation of the choroidal vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…39 Similarly, our findings showed that higher IOP was significantly related to lower CVI, although many studies suggest that CVI is relatively unaffected by various factors. 14,15 We hypothesize that elevated IOP has a mechanical effect on the choroid and its vascularity. The hypothesized mechanism is that high IOP can cause mechanical stress and deformation of the choroidal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…The process of obtaining CVI is shown in Figure 1. This was described in detail in previous articles 15 . The CVI is defined as the proportion of the LA to the TCA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations